Mathematics Addendum - class 5 - Galhenage Iranga,Don Celsus Shenal; Ms.Nosheen Hsaan; Ms.Sidddiqua Maqsood (Ideal Furnishers, 2022)
This addendum supplements the Class 4 mathematics curriculum, focusing on key concepts and providing additional resources and activities to enhance student understanding. It covers essential topics such as number sense, operations (addition, subtraction, multiplication, division), fractions, decimals, measurement, geometry, and basic data interpretation. Recommended activities include hands-on projects, math games, and real-life applications to engage students and reinforce their learning. The goal is to foster a deeper appreciation for mathematics and encourage curiosity and problem-solving skills, laying a strong foundation for future studies.
This addendum is designed to support and enhance the learning experience for Class 4 students in mathematics. By integrating additional resources and activities, we aim to foster a deeper understanding and appreciation for the subject. Encouraging curiosity and problem-solving will help students build a strong foundation for future mathematical learning.
Keywords: Multiplication; Data Collection